2015
DOI: 10.1007/s10658-015-0606-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of abiotic stresses on the protection efficacy of defence elicitors and on metabolic regulation in tomato leaves infected by Botrytis cinerea

Abstract: Finding sustainable plant protection strategies is a major challenge for agriculture. Taking advantage of the plant natural immune system by using plant defence elicitors is an interesting avenue to explore. However, transfer to field application is often difficult, mostly due to the complexity of interactions between plants and their environment, involving biotic and abiotic stresses. The protection efficacy against gray mold and the modes of action of potential elicitors were studied on tomato. Modulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The use of BE can be considered a promising strategy to help the plant under conditions of abiotic and biotic stress (Ben Salah et al, 2018;Santaniello et al, 2017;Shukla et al, 2017). Maymoune et al (2015) observed that the application of BE of green algae (Ulva sp.) decreased the necrosis diameter, inhibited spore germination, and increased protection efficacy in tomato plants (Solanum lycopersicum L.) infected with Botrytis cinerea under water stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The use of BE can be considered a promising strategy to help the plant under conditions of abiotic and biotic stress (Ben Salah et al, 2018;Santaniello et al, 2017;Shukla et al, 2017). Maymoune et al (2015) observed that the application of BE of green algae (Ulva sp.) decreased the necrosis diameter, inhibited spore germination, and increased protection efficacy in tomato plants (Solanum lycopersicum L.) infected with Botrytis cinerea under water stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco is a cold-sensitive plant, which also serves as a good model to study plant chilling damage. Several studies agree that BABA can alleviate different biological and abiotic stresses including Colletotrichum orbiculare, water stress, gray mold, and Phytophthora infestans, among others (Jeun et al, 2007;Macarisin et al, 2009;Maymoune et al, 2015;Wang et al, 2015;Kuźnicki et al, 2019). However, less information is available about the effect of BABA on plant defense against low temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Beta-aminobutyric acid (BABA), widely described as a defense-priming molecule, confers plant resistance to a broad spectrum of biotic and abiotic stresses including microbial pathogens, arthropods, salt, and heat shock (Maymoune et al, 2015;Mostek et al, 2016;Yao et al, 2019). Prior research confirmed that BABA helps soybean to combat Cd stress and barley to resist salt stress.…”
Section: Introductionmentioning
confidence: 99%